O gênero resumo de texto no livro didático do nono ano : análise e proposta de intervenção - Rocha, Édila Regina da Silva (2015)
The theme of current research deals with the teaching of discursive genres in Fundamental Teaching ll and specifically copes with the production of summaries in the Portuguese Language classroom within the concept of language as a form of interaction in the context of Applied Linguistics. Although known and widely employed by teachers of Basic Education, the genre "summary" proves to be one of the most difficult to write. In fact, students, ranging from Basic Education to the Entrance Exams for admittance to higher education, have a low performance in its production. Further, the use of the genre in the classroom by teachers of different disciplines proves to be highly confusing and incoherent (Machado, 2007)-The main aim of current dissertation, derived from a Profletras Master's research, is to forward an intervention proposal on the genre "summary", through a didactic sequence, for the 9th year History class in a government-run school in the northwestern region of the state of Parana, Brazil. Current research's specific aims are: (1) prepare a theoretical synthesis that may be employed by teachers of several disciplines (History, Geography, Sciences and others); (2) discuss the idea of summary with 9th year students; (3) characterize the strategies for writing a summary. The theory is foregrounded on Social Interaction (BAKHTlN; VOLOSHINOV, 1992; BAKHTIN, 1997) and on Socio-discursive Interaction, with special reference to research by Dolz and Schneuwly (1998), Machado (2007) and others. Results show that the production of a good summary is the resultof reading practice of production conditions, theme, composition structure, linguistic-discursive markers, summarization strategies, and selection of the discursive genre which will be the summary's source text. It is also the result of interdisciplinary effort and the mediation of teachers of Portuguese.